Black Hole Philosophy - Romero, Gustavo Esteban (2021)
Black holes are arguably the most extraordinary physical objects we know in the universe. Despite our thorough knowledge of black hole dynamics and our ability to solve Einstein’s equations in situations of ever increasing complexity, the deeper implications of the very existence of black holes for our understanding of space, time, causality, information, and many other things remain poorly understood. In this paper I survey some of these problems. If something is going to be clear from my presentation, I hope it will be that around black holes science and metaphysics become more interwoven than anywhere else in the universe.